Mass-Circulation Ukrainian Newspapers in the System of the Soviet Press (1920 s - early 1930 s) - Vakulchuk Olha (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2020)

(untitled)
This article considers the development of the specific type of the Soviet press - mass-circulation newspapers in the 1920s - early 1930s, and the possibility of using them as a historical source. The way mass-circulation periodicals operate, as well as their place and role in the system of the Soviet press are characterized in the light of social and political situation in Ukraine in the 1920s - early 1930s. Possibilities of bibliographic processing of this type of periodicals, creation of printed bibliographic indexes, catalogs and electronic databases are also considered. 1920s - 1930s was the period most favorable for the formation and development of the Soviet mass-circulation press performing the functions of propagandist, organizer and agitator from the very start. The mass-circulation press was not only supported by the Communist Party, but also tightly controlled by it. All the mass-circulation newspapers of that time were focused on covering certain topics in publications: labor successes and achievements of the country and the republic, labor successes and achievements of a separate enterprise, institution, and education institution. The main intention was to influence the motivation to work, to create the mood of labor drive, enthusiasm, and a sense of unity in the team. Multi-circulation newspapers almost stenographically transcribed all the events and activities that took place in the country and at a single enterprise, collective farm, institution, school. They all wrote about industrialization, Five Year Plan, social competitions, counter-plans, shock workers, efficiency experts, tasks of party teams, voluntary Saturday work «subbotniks», standardization of working hours, etc. Other pressing issues at that time were the fight against religion and mismanagement, elections and re-elections to city councils, mass cultural and education work, collective agreements, training, assistance to peasants, and so on. Theoretical and practical principles of origin, development and operation of the mass-circulation press, organization of its storage in library funds, access to this information resource require thorough research. The problem of bibliographic reconstruction of the mass-circulation press in particular, and the period of the 1920s - 1930s, remains unsolved. Therefore, given the significant source potential of the mass-circulation press, its historical and bibliographic research at the present stage is a critical task.